Chest Wall Regional Anesthesia for Modified Radical Mastectomy and Axillary Lymph Node Dissection: A Case Report. Issue 6 (June 2021) - Bhakta, Pradipta; Mac Sweeney, Kevin; O'Donnell, Brian D.
Abstract : Restrictive chest wall disorders impair cardiopulmonary physiology and pose anesthesia-related safety challenges. Regional anesthesia, as the primary anesthetic modality, may mitigate general anesthesia-related risks in such patients presenting for breast cancer surgery. We describe the use of chest wall fascial plane blocks as the primary anesthetic, combined with high-flow humidified nasal oxygen and low-dose propofol sedation, in a patient with complex comorbidities presenting for modified radical mastectomy and axillary lymph node dissection. Abstract : Supplemental Digital Content is available in the text.